A certificateless designated verifier sanitizable signature - ZHAN, Yonghua (Institutional Knowledge at Singapore Management University, 2023)
Sanitizable Signature is a digital signature variant that enables modification operations, allowing sanitizers to alter the signed data in a regulated manner without requiring any interaction with the original signer. It is widely used in scenarios such as healthcare data privacy protection, social networks, secure routing, etc. In existing sanitizable signature schemes, anyone can verify the validity and authenticity of the sanitized message, which results in costly certificate management overhead or complicated key escrow problems. To address these challenges, a designated verifier certificateless sanitizable signature scheme is proposed. This scheme introduces the concept of a designated verifier into sanitizable signatures, allowing sanitizers to specify verifier for the sanitized message. Only the specified verifiers can verify the validity of the message/signature pair, ensuring that the message information remains confidential to parties other than the designated verifiers. Security analysis demonstrates that the proposed scheme satisfies the properties of unforgeability, immutability, privacy and non-transferability. Comparative analysis demonstrates that the proposed scheme provides additional support for designated verifiers compared to traditional sanitizable signature schemes, while eliminating certificate management and key escrow issues. We have conducted an experiment, and the results demonstrate that the proposed scheme displays excellent efficiency.